FTK Image For Forensic Data Processing In Forensic Tools - Rachmat Suryadithia; Witriana Endah Pangesti; Muhammad Faisal; Aji Nurrohman; W Wibisono; Arman Syah Putra (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The background of this research is how the use of a software can help find forensic data, which is needed so that the tool used is the right tool in helping forensic problems. The method used in this study is the NIJ method using 5 stages in a process of determining the answer. The first stage is preparation, the second stage in collecting data, the third is testing and the fourth stage is analyzing and the last is the reporting stage with the five stages. The direction of the research will be clearer. The problem raised in this research is how to find evidence using FTK images software. Using this software, you can search for the desired forensic data so that it can be proven that there is forensic evidence. The purpose of this study is how to prove data, especially photo data, can be used as forensic data that can be used as evidence, by using the right tools, namely the existing FTK images software, with the software, it can help parties in proving, especially in terms of forensics